Bebida láctea fermentada utilizando lactosuero como sustituto parcial de leche y diferentes estabilizantes comerciales - Zambrano Arias, Carlos Gerardo (2013)
The general objective of this investigation consisted in giving added value to breast-feed serum, a byproduct that is wasted by the ESPAM's workshops during the lactic processes and it can be suitable, at present generating a high contamination to the ecosystem and economic losses to the ESPAM-MFL; A Completed Random Design was used at AxB with three replicates. The factors of study were: A. Percentages breast-feed serum (10, 20 and 30 %) in combination with milk and B. stabilizers ( Obsigel 8AGT, Obsigel 955B and CC 729, all to the 0,1 % ); The witness was a natural sugared yogurt. Treatments I was done the physical chemical analyses after bottled, they used 500 ml's in 162 experimental units for a total of 9 treatments, besides the organoleptical analysis with 30 judges were qualified following attributes accomplished an evaluation itself: Texture, aroma, taste, general quality. The best treatment regarding the physique and chemical variable: PH 4,17% acidity 0,67, consistence 3,13 cm3, Brix 15,23. The sensorial analysis to all treatments had very good acceptance being statistically equal.